A Novel One-Dimensional Copper Mellitate Complex Featured by {Cu(H2O)2(urea)[C6(COO)4(COOH)2]}n2n- Polyanions - Köferstein, Roberto; Robl, Christian (Zeitschrift für anorganische und allgemeine Chemie (1950), 2015)
Blue monoclinic single crystals of the novel one‐dimensional [H3N‐(CH2)6‐NH3][Cu(H2O)2(urea)(μ2‐C6(COO)4(COOH)2)]·H2O coordination polymer were prepared in aqueous solution at room temperature in the presence of 1,6‐diaminohexane and urea [space group P21/n (no. 14) with a = 958.48(9), b = 1465.74(11), c = 1821.14(12) pm, β = 97.655(8)°]. The Cu2+ cation is coordinated in a square pyramidal manner by two oxygen atoms stemming from the dihydrogen mellitate tetraanion, one oxygen atom from the urea molecule, and two water molecules. The Cu–O distances are in the range of 193.3(2) and 229.4(2) pm. The connection between Cu2+ and [C6(COO)4(COOH)2]4– yields infinite chain‐like polyanions parallel to [1$\bar{}$01] with a composition of {Cu(H2O)2(urea)[C6(COO)4(COOH)2]}n2n–. The dihydrogen mellitate tetraanion adopts a μ2 coordination mode. The [(H3N–(CH2)6–NH3)]2+ cations are accommodated between the chains as counter cations. The hexane‐1,6‐diammonium cations adopt a partial synclinal conformation. The chains are connected by strong and weak hydrogen bonds. Magnetic measurements reveal a paramagnetic Curie‐Weiss behavior and a magnetic moment of 1.93 μB per Cu2+. Thermoanalytical investigations in air show that the complex is stable up to 135 °C, and the following decomposition processes yield CuO.